2016
DOI: 10.1016/j.bpj.2015.11.1932
|View full text |Cite
|
Sign up to set email alerts
|

Structural Ensembles of Intrinsically Disordered Proteins Depend Strongly on Force Field: A Comparison to Experiment

Abstract: Cytoplasmic dynein is a protein complex responsible for transporting cellular cargos on microtubules. Dynein's activities are regulated by other proteins including dynactin which mediates dynein-cargo interactions and increases dynein's processivity. The intermediate chain (IC) of dynein binds to dynactin p150Glued subunit, an interaction central to dynein regulation. The N-terminal domain of IC, N-IC is partially disordered, and contains binding site for a coiled-coil domain of p150Glued and a serine-rich reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(68 citation statements)
references
References 0 publications
3
63
2
Order By: Relevance
“…A number of studies have been performed to compare force fields and it is now clear that force fields have become better in the last years in modeling folded proteins and even to study the folding of proteins . However, it is still under debate if force fields are accurate enough to represent IDPs . In this study, we test by means of REMD simulations whether modern force fields are able to capture the conformational ensemble of A β42, an IDP associated with Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been performed to compare force fields and it is now clear that force fields have become better in the last years in modeling folded proteins and even to study the folding of proteins . However, it is still under debate if force fields are accurate enough to represent IDPs . In this study, we test by means of REMD simulations whether modern force fields are able to capture the conformational ensemble of A β42, an IDP associated with Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, computer simulations, often in conjunction with experimental data, are essential in understanding the dynamics of IDPs. In particular, explicit solvent atomistic molecular dynamics (MD) simulations have been used to study a multitude of IDPs …”
Section: Introductionmentioning
confidence: 99%
“…522−525 Similarly as in the field of protein folding, the major challenge in IDP simulation is the efficient treatment of large time scale dynamics, while maintaining sufficient accuracy. 525 In the past decade, the KIX/pKID system 526 has become a model protein complex for computational studies of the folding and binding of a disordered protein.…”
Section: Protein Interactionsmentioning
confidence: 99%
“…It was found that the folding mechanism and the properties of the unfolded state depended substantially on the choice of force field. Another extensive and more recent study [2] concluded, from a millisecond of simulations on intrinsically disordered proteins, that eight well-known force fields generate unexpectedly huge differences in chain dimension, hydrogen bonding and secondary structure content. In fact, discrepancies are so serious that changing the force field has a stronger effect on secondary structure content than changing the entire peptide sequence.…”
Section: Introductionmentioning
confidence: 99%